Evaluation of the airway microbiome in nontuberculous mycobacteria disease. Issue 4 (25th October 2018) - Sulaiman, Imran; Wu, Benjamin G.; Li, Yonghua; Scott, Adrienne S.; Malecha, Patrick; Scaglione, Benjamin; Wang, Jing; Basavaraj, Ashwin; Chung, Samuel; Bantis, Katrina; Carpenito, Joseph; Clemente, Jose C.; et al.
Aspiration is associated with nontuberculous mycobacterial (NTM) pulmonary disease and airway dysbiosis is associated with increased inflammation. We examined whether NTM disease was associated with a distinct airway microbiota and immune profile. 297 oral wash and induced sputum samples were collected from 106 participants with respiratory symptoms and imaging abnormalities compatible with NTM. Lower airway samples were obtained in 20 participants undergoing bronchoscopy. 16S rRNA gene and nested mycobacteriome sequencing approaches characterised microbiota composition. In addition, inflammatory profiles of lower airway samples were examined. The prevalence of NTM + cultures was 58%. Few changes were noted in microbiota characteristics or composition in oral wash and sputum samples among groups. Among NTM + samples, 27% of the lower airway samples were enriched with Mycobacterium . A mycobacteriome approach identified Mycobacterium in a greater percentage of samples, including some nonpathogenic strains. In NTM + lower airway samples, taxa identified as oral commensals were associated with increased inflammatory biomarkers. The 16S rRNA gene sequencing approach is not sensitive in identifying NTM among airway samples that are culture-positive. However, associations between lower airway inflammation and microbiota signatures suggest a potential role for these microbes in the inflammatory process in NTM disease. 16S rRNA gene sequencing is not sensitive to detect Mycobacterium but identifies microbiota signatures associated with inflammation http://ow.ly/opXm30ldtQH